The consumers awareness, perception and attitute towards cosmetic products and skin condition assessments among the population of Kuantan, Pahang - Nur Ain binti Ayob (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2016)
The increased usage of cosmetic products has caused a growing concern and yet little is known about cosmetics from consumers' perspective. This study aimed to explore consumers' perspectives towards cosmetic products, to develop a valid and reliable tool for assessing consumers' awareness, perceptions and attitudes towards cosmetic products, to assess consumers' awareness, perceptions and attitudes towards cosmetic products, to investigate consumers' skin condition, to identify any possible differences between; awareness, perceptions, attitudes and skin conditions with respect to their demographic background, and to identify any associations between consumers' awareness, perceptions, and attitudes with skin conditions. Cross-sectional study design was used and carried out among the residence in Kuantan. To begin, an interview guide was developed and in-depth face-to-face interviews were conducted. The conversations were recorded in audio and transcribed verbatim. Next, a questionnaire was developed and piloted among 66 consumers. Reliability, internal consistency and other statistical analyses were analyzed. For the final stage, a total number of 551 consumers were recruited conveniently. They were subjected to fill up the questionnaire and do the skin condition assessments; collagen intensity, elasticity, melanin, hydration and trans epidermal water loss. Statistical analyses were carried out to the data where it is appropriate. The results from the interview session show that, awareness related to the cosmetic products in Malaysia among the consumers was not satisfying. Although, at the time of the study, they were using conventional cosmetic products, consumers showed a positive perception and attitude towards natural and halal cosmetic products. However, price and accessibility of those products may influence their purchase intention. For the pilot study, it was found that the questionnaire can be used as a valid and reliable tool for assessing consumers' awareness, perceptions and attitudes towards cosmetic products in Malaysia in future studies. In the final stage, consumers in this study were found to have adequate level of awareness, held positive perceptions and practiced positive attitudes towards the cosmetic product. Subsequently, consumers in this study were found to have; high collagen intensity, more elastic skin and low TEWL value. However, moisture content and melanin content were found to be low. Cosmetic consumers' demographic background such as gender and age was found to have significant differences towards their awareness, perception, attitude and skin conditions. Lastly, consumers with adequate awareness were associated with low melanin content and consumers with positive perception were associated with; low melanin content and insufficiently moisture skin. To conclude, consumers should be wise in terms of using the cosmetic products in their daily life.